2018
DOI: 10.18203/2320-1770.ijrcog20181933
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of efficacy and safety of intravenous ferric carboxymaltose versus iron sucrose in the treatment of iron deficiency anaemia of pregnancy in a tertiary care hospital

Abstract: Background: Anaemia is a global public health problem. To optimize iron delivery in pregnancy, new intravenous complexes like Ferric carboxymaltose (FCM) have been developed in the few years. This study aims to compare the efficacy and safety of FCM vs the iron sucrose during pregnancy.Methods: This study was conducted in the Department of Obstetrics and Gynaecology, Shri Maharaja Gulab Singh (S.M.G.S.) Hospital, Government Medical College Jammu, Jammu and Kashmir over a period of 1 year. 100 pregnant females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…On administering, it allows for controlled delivery of iron within the cells of the reticuloendothelial system and subsequent delivery to the iron-binding proteins ferritin and transferrin, with minimal risk of release of large amounts of ionic iron in the serum thus allows rapid administration of high doses of iron in a single sitting. 5 We observed higher increase in haemoglobin in FCM group than iron sucrose group at each point of measurement. The mean rise in haemoglobin values from baseline in the FCM group was 0.20±0.06 at 3 rd day, 2.03±0.47 at 3 weeks, 3.86±0.53 at 12 weeks compared to iron sucrose group, which was 0.11±0.08 at 3 rd day, 1.51±0.39 at 3 weeks, and 3.22±0.54 at 12 weeks, which was statistically significant and showed that the haemoglobin levels were increased more in FCM group.…”
Section: Discussionmentioning
confidence: 51%
“…On administering, it allows for controlled delivery of iron within the cells of the reticuloendothelial system and subsequent delivery to the iron-binding proteins ferritin and transferrin, with minimal risk of release of large amounts of ionic iron in the serum thus allows rapid administration of high doses of iron in a single sitting. 5 We observed higher increase in haemoglobin in FCM group than iron sucrose group at each point of measurement. The mean rise in haemoglobin values from baseline in the FCM group was 0.20±0.06 at 3 rd day, 2.03±0.47 at 3 weeks, 3.86±0.53 at 12 weeks compared to iron sucrose group, which was 0.11±0.08 at 3 rd day, 1.51±0.39 at 3 weeks, and 3.22±0.54 at 12 weeks, which was statistically significant and showed that the haemoglobin levels were increased more in FCM group.…”
Section: Discussionmentioning
confidence: 51%
“…1 ). A total of 18 articles that addressed one or more of the outcomes were included of which seven studies compared iv FCM and iv ISC (five RCTs 7 16 17 18 19 and two retrospective audits) 20 21 and 11 were observational studies 22 23 24 25 26 27 28 29 30 31 32 on safety and effectiveness of iv FCM.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the five RCTs, four were conducted in India 7 16 17 19 and one in Pakistan 18 . One retrospective audit each from Switzerland 20 and Australia 21 were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations